2008
DOI: 10.1007/s11557-008-0579-8
|View full text |Cite
|
Sign up to set email alerts
|

Positive association between mycorrhiza and foliar endophytes in Poa bonariensis, a native grass

Abstract: The interaction between mycorrhiza and leaf endophytes (Neotyphodium sp.) was studied in three Poa bonariensis populations, a native grass, differing significantly in endophyte infection. The association between endophytes and mycorrhizal fungi colonisation was assessed by analysing plant roots collected from the field. We found that roots from endophyte-infected populations showed a significantly higher frequency of colonisation by mycorrhizal fungi and that soil parameters were not related to endophyte infec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(11 citation statements)
references
References 44 publications
1
8
0
Order By: Relevance
“…Soteras et al (2013) reported that higher colonization percentage of dark septate endophyte in root Polyepis australis decreasing the colonization of arbuscular mycorrhiza fungi. Furthermore, this result relevant to the assumtion that the colonization of root and foliar endophytes also correlated with colonization of arbuscular mycorrhiza (Novas et al 2009;Eschen et al 2010). Therefore, we can generated that the colonization of root endophytes influenced plant-mycorrhiza.…”
Section: Resultsmentioning
confidence: 51%
“…Soteras et al (2013) reported that higher colonization percentage of dark septate endophyte in root Polyepis australis decreasing the colonization of arbuscular mycorrhiza fungi. Furthermore, this result relevant to the assumtion that the colonization of root and foliar endophytes also correlated with colonization of arbuscular mycorrhiza (Novas et al 2009;Eschen et al 2010). Therefore, we can generated that the colonization of root endophytes influenced plant-mycorrhiza.…”
Section: Resultsmentioning
confidence: 51%
“…and Poa spp.) [131][132][133][134][135][136][137][138][139][140]. Further complexities also exist with regard to species interactions [141,142].…”
Section: Interaction Of Epichloë Endophytes With Other Taxamentioning
confidence: 99%
“…In agronomic grasses, i.e., tall fescue, and annual and perennial ryegrass, endophyte infection has been shown to inhibit colonization by AM fungi [133][134][135][136]. Similarly, beneficial effects of epichloid endophytes on the frequency of root colonization by AM fungi have been reported in several wild grasses from Argentina, i.e., Bromus setifolius [137] and Poa bonariensis [138]. The four-way interactions among grass hosts, epichloid endophytes, AM fungi, and herbivores may alter herbivory and herbivore population dynamics [139].…”
Section: Mechanisms Of Endophyte-induced Tolerance To Biotic Stressesmentioning
confidence: 99%